2019
DOI: 10.18488/journal.aefr.2019.95.581.603
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aid and Macroeconomic Policy on Growth in Nigeria: A Bounds Testing Approach

Abstract: This paper explores the impact of aid and macroeconomic policy on growth with Nigeria as a case study. Given its limited use in the aid efficiency literature on Nigeria, the autoregressive distributed lag (ARDL) model was applied in this study for time series data covering 44 years (1970-2014) in an attempt to expand the use of this approach and to check if a similar (negative) relationship is found between aid and growth. The results showed a positive correlation i.e. aid supports growth in Nigeria in the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…As government spending increases, the unemployment level rises, this may be due to the structure and institutional setting of government instrument in SSA. This result is in consonance with the finding that suggested higher government size slowdown economic performance (Schaltegger and Torgler, 2006; Gregoriou and Ghosh, 2009; Usman et al. , 2011).…”
Section: Empirical Results and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As government spending increases, the unemployment level rises, this may be due to the structure and institutional setting of government instrument in SSA. This result is in consonance with the finding that suggested higher government size slowdown economic performance (Schaltegger and Torgler, 2006; Gregoriou and Ghosh, 2009; Usman et al. , 2011).…”
Section: Empirical Results and Discussionsupporting
confidence: 90%
“…Studies have revealed economic advantages of increasing government size (Sedrakyan and Candamio, 2019; Gisore et al. , 2014; Patricia and Izuhukwu, 2013; Afonso and Jalles, 2011) but not without limitations (Usman et al. , 2011; Folster and Henrekson, 2001; Cashin, 1995; Gregoriou and Ghosh, 2009), especially in developing regions like Africa where limited tax base and macroeconomic uncertainty are the attributes of most economies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the developing countries including Nigeria have attracted special attention on fiscal view of inflation as a result of general notion that inefficient tax collection, political instability and limited access to external borrowing are predominant challenges of developing nations. These tend to reduce the relative cost of seigniorage and raise dependence on the inflation tax (Cukierman et al, 1992;Calvo and Vegh, 1999;Alesina and Drazen, 1991 ;Usman and Apinran, 2019). Empirically, the studies conducted among developing economies reveal existence of significant affiliation between inflation and fiscal deficit especially in high inflation countries (Metin, 1998;Domaç and Yücel, 2005;De Haan and Zelhorst, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Also, some studies have examined how macroeconomic factors such as economic growth, globalisation, ecological footprint, financial development and other influences electricity consumption (Rafindadi & Ozturk, 2016; Rafindadi & Usman, 2021). For example, Usman (2011) uses the Nonlinear ARDL model as an estimation strategy to examine the effects of economic growth, globalisation and ecological footprint on sustainable electricity consumption in Brazil. Findings from this study reveal that both positive and negative changes to economic growth, and globalisation increase electricity consumption.…”
Section: Literature Review and Contributionmentioning
confidence: 99%